Efficient production of isomelezitose by a glucosyltransferase activity in Metschnikowia reukaufii cell extracts. Issue 6 (1st October 2019) - Garcia‐Gonzalez, Martin; Plou, Francisco J.; Cervantes, Fadia V.; Remacha, Miguel; Poveda, Ana; Jiménez‐Barbero, Jesús; Fernandez‐Lobato, Maria
Summary: Metschnikowia reukaufii is a widespread yeast able to grow in the plants' floral nectaries, an environment of extreme conditions with sucrose concentrations exceeding 400 g l −1, which led us into the search for enzymatic activities involved in this sugar use/transformation. New oligosaccharides were produced by transglucosylation processes employing M. reukaufii cell extracts in overload‐sucrose reactions. These products were purified and structurally characterized by MS‐ESI and NMR techniques. The reaction mixture included new sugars showing a great variety of glycosidic bonds including α‐(1→1), α‐(1→3) and α‐(1→6) linkages. The main product synthesized was the trisaccharide isomelezitose, whose maximum concentration reached 81 g l −1, the highest amount reported for any unmodified enzyme or microbial extract. In addition, 51 g l −1 of the disaccharide trehalulose was also produced. Both sugars show potential nutraceutical and prebiotic properties. Interestingly, the sugar mixture obtained in the biosynthetic reactions also contained oligosaccharides such as esculose, a rare trisaccharide with no previous NMR structure elucidation, as well as erlose, melezitose and theanderose. All the sugars produced are naturally found in honey. These compounds are of biotechnological interest due to their potential food, cosmeceutical and pharmaceutical applications. Abstract : New oligosaccharides produced by sucrose transglucosylation employing Metschnikowia reukaufii cell extracts Overproduction of isomelezitose NMR structure elucidation of the rare trisaccharide esculose.